Adverse effect of FTY720P on colonic Na+/K+ ATPase is mediated via ERK, p38MAPK, PKC, and PI3K. Issue 2 (17th August 2022) - Rida, Reem; Hodeify, Rawad; Kreydiyyeh, Sawsan
Abstract: FTY720P, an analogue of sphingosine 1‐phosphate, has emerged lately as a potential causative agent of inflammatory bowel disease, in which electrolytes movements driven by the sodium gradient established by the Na + /K + ATPase are altered. We showed previously in Caco‐2 cells, a 50% FTY720P‐induced decrease in the ATPase activity, mediated via S1PR2 and PGE2. This work aims at delineating the mechanism underlying PGE2 release and at investigating if the ATPase inhibition is due to changes in its abundance. The activity of the ATPase and the localization of a GFP‐tagged Na + /K + ‐ATPase α1 ‐subunit were assessed in cells treated with 7.5 nM FTY720P. The involvement of ERK, p38 MAPK, PKC, and PI3K was studied in cells treated with 7.5 nM FTY720P or 1 nM PGE2 in presence of their inhibitors, or by determining changes in the protein expression of their activated phosphorylated forms. Imaging data showed ∼30% reduction in the GFP‐tagged Na + /K + ATPase at the plasma membrane. Both FTY720P and PGE2 showed, respectively, 50% and 60% reduction in ATPase activity that disappeared when p38 MAPK, PKC, and PI3K were inhibited individually but not with ERK inhibition. The effect of FTY720P was imitated by PMA, an activator of PKC. Western blotting revealed inhibition of ERK by FTY720P. It was concluded that FTY720P, through activation of S1PR2, downregulates the Na + /K + ATPase by inhibiting ERK, which in turn activates p38 MAPK leading to the sequential activation of PKC and PI3K, PGE2 release, and a decrease in the Na + /K + ATPase activity and membrane abundance. Abstract : We showed previously in Caco‐2 cells, a significant FTY720P‐induced decrease in the Na + /K + ATPase activity, mediated via PGE2. Fluorescence imaging of GFP‐tagged Na + /K + ATPase showed that the reduced ATPase activity is due to a lower membrane abundance and is mediated through activation of S1PR2, which inhibits ERK. The latter activates p38 MAPK leading to the sequential activation of PKC, PI3K, PGE2 release, and downregulation of the Na + /K + ATPase.